Highly Processable Covalent Organic Framework Gel Electrolyte Enabled by Side‐Chain Engineering for Lithium‐Ion Batteries - Liu, Ziya; Zhang, Kun; Huang, Guoji; Xu, Bingqing; Hong, You‐lee; Wu, Xiaowei; Nishiyama, Yusuke; Horike, Satoshi; Zhang, Gen; Kitagawa, Susumu (Angewandte Chemie International Edition, 2022)
Although covalent organic frameworks (COFs) with a graphene‐like structure present unique chemical and physical properties, they are essentially insoluble and infusible crystalline powders with poor processability, hindering their further practical applications. How to improve the processability of COF materials is a major challenge in this field. In this contribution, we proposed a general side‐chain engineering strategy to construct a gel‐state COF with high processability. This method takes advantages of large and soft branched alkyl side chains as internal plasticizers to achieve the gelation of the COF. We systematically studied the influence of the length of the side chain on the COF gel formation. Benefitting from their machinability and flexibility, this novel COF gel can be easily processed into gel‐type electrolytes with specific shape and thickness, which were further applied to assemble lithium‐ion batteries that exhibited high cycling stability. We propose a general gelation strategy for the construction of highly processible covalent organic framework (COF)‐Gel materials through side‐chain engineering. The COF‐Gel is compatible with electronic devices with diverse functionality, including in lithium‐ion batteries.